Comparing Moderna’s mRNA-1083 and Pfizer’s dual-target mRNA vaccines for influenza and COVID-19 - Adewunmi Akingbola; Abiodun Adegbesan; Kolade Adegoke; Courage Idahor; Petra Mariaria; Favour Peters; Raolat Adenike Salami; Olajide Ojo; Emmanuel Nwaeze; Owolabi Abdullahi; Joel Chuku (npj Vaccines)
Abstract This review examines Moderna’s mRNA-1083 and Pfizer/BioNTech’s mRNA-1020/1030 dual-target vaccines for COVID-19 and influenza. Both utilize mRNA technology, demonstrating strong immunogenicity and favorable safety profiles. Moderna’s mRNA-1083 showed superior immune responses, while Pfizer’s mRNA-1020/1030 performed well but was slightly less effective against influenza B. These vaccines simplify immunization strategies, enhance protection, and emphasize the need for global vaccine equity to prevent future outbreaks.